G199(P) Single centre service evaluation to determine appropriate use of faecal calprotectin testing in children. (24th May 2017) - Sandhu, K; Macdonald, D; Rampton, D; Naik, S
Abstract : Aim: There are currently no faecal calprotectin (FCP) request guidelines. We informally adopted the adult guidelines with amendments including age >5 years with chronic abdominal pain and diarrhoea and annual assessment of inflammatory bowel disease (IBD) patients on anti-TNF/immunosuppressants to continue or stop treatment. We evaluated FCP requests made in children in 2015 in a tertiary gastroenterology unit as per amended inhouse adult FCP guidelines below: Chronic abdominal pain with non-bloody diarrhoea and weight loss in patients>5 years Known IBD outpatient with diarrhoea Annual assessment of patient with IBD on anti-TNF/immunosuppressant with no symptoms and normal bloods Known IBD with non-specific symptoms (eg fatigue, abdominal pain, anaemia) Methods: We retrospectively reviewed clinic letters, reasons for FCP requests and investigations of patients<18 years in whom FCP was requested from January to December 2015. Results: 219 FCP requests were made. Nine patients were excluded as there was incomplete information available. Majority of FCP requests (90%) were made in outpatients with 56% made by the paediatric gastroenterology team. Requests were also made by general paediatricians (20%), GP's (20%) and other specialities (4%). The main indication for requesting FCP was chronic abdominal pain and diarrhoea in both the gastroenterology team and other specialities. Other indications included known IBD with possible flare and known IBD for assessment regarding weaning or stopping medication. Appropriate FCP requests were made in 132 patients (63%) and inappropriate in 78 patients (37%). Thirty-five percent (41/117) of the FCP requests were made by the gastro team and 40% (37/93) requests by non-gastro teams were inappropriate. Main reason for inappropriate requests in the gastroenterology team was ordering scope simultaneously with FCP (17 patients) and in the non-gastro teams was PR bleeding (18 patients). 51 requests (24%) were ordered in patients known to have IBD. In this cohort 26 patients avoided colonoscopy on the basis of symptoms, bloods and FCP result. Conclusion: Our results show there is a need to develop paediatric FCP request guidelines in order to reduce the number of inappropriate requests and colonoscopies. A guideline will improve cost effectiveness and optimise the use of FCP.